Hubungan Status Pekerjaan dan Lama Pemakaian Kontrasepsi Suntik DMPA (Depot Medroxy Progesteron Acetat) dengan Kenaikan Berat Badan Akseptor di Wilayah Kerja Puskesmas Jati Raya Kota Kendari - Amiruddin Amiruddin; Ahdiat Agriansyah; Yarni Indryanti (bionature, 2022)
Abstract. Based on the preliminary observation to the mothers using injection contraception type DMPA had experience on gaining the weight. The purpose of the study was to find out the statust of work and the duration of the use of injection contraception type DMPA with the gain weight to the acceptors. The study was and association by involving the design of cross-sectional study. The population of the study was 80 acceptors. Sample was taken by purpossive sampling totalling 65 respondents by giving the observation sheets and interviewing. Result of the study shown that the status of work with weight was categorized in working about 50 respondents (76,9 %) and the duration of use was 9 months totalling 20 respondents (30,8 %). Result of analysis by using the test of chi-square concluded that there tatus of work was no significant effect to weight of the respondents of contraception type DMPA injection (p > 0,05), while the duration of use was significant effect to weight of the respondents of contraception type DMPA injection (p <0 , 05). Keywords: job, duration of use, weigh, injection of DMPA.